In vitro induction of trained immunity in adherent human monocytes - Jorge Domínguez-Andrés (STAR Protocols, 2021)
Summary: A growing number of studies show that innate immune cells can undergo functional reprogramming, facilitating a faster and enhanced response to heterologous secondary stimuli. This concept has been termed “trained immunity.” We outline here a protocol to recapitulate this in vitro using adherent monocytes from consecutive isolation of peripheral blood mononuclear cells. The induction of trained immunity and the associated functional reprogramming of monocytes is described in detail using β-glucan (from Candida albicans) and Bacillus Calmette-Guérin as examples.For complete details on the use and execution of this protocol, please refer to Repnik et al. (2003) and Bekkering et al. (2016).